Clinical risk profile for a second anterior cruciate ligament injury in female soccer players after anterior cruciate ligament reconstruction - Fältström, A.; Kvist, J.; Bittencourt, N. F. N.; Mendonça, L. D.; Hägglund, M. (The American Journal of Sports Medicine, 2021)
Background: The risk of a second anterior cruciate ligament (ACL) injury when participating in pivoting sports after ACL reconstruction is high. Risk factors associated with a second ACL injury are complex.